The impact of the real interest rate on green investment: evidence from the United States - Van Den Engel, Anouk; Swart, Julia; Schramm, Marc (Journal of Business Economics and Management, 2024)
Monetary policy has an impact on CO2 emissions which is not entirely understood in the literature. Whereas there is a consensus that the impact is indirect through investments, the literature does not investigate the impact of monetary policy on (green) investments. Additionally, we argue in this paper that monetary policy can have a different impact on ‘green’ investments and ‘brown’ investments. This paper focuses, therefore, on the impact of monetary policy on investments. In particular, this paper empirically investigates whether the real interest rate has a different effect on green investment, compared to general investment, using quarterly data from the United States between 2004 and 2020. The results from the autoregressive distributed lag model show that the real interest rate is negatively related to the ratio of green investment relative to total investment. This result emphasizes the importance of the green investment effect channel and suggests that monetary policy has an unintentional role in climate policy which should be considered by policy makers.